THE ROLE OF LEADERSHIP IN SUPPORTING ARTIFICIAL INTELLIGENCE (AI) INTEGRATION IN ORGANIZATIONS - Zamir, Noor Azizah (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2025)
The rapid integration of Artificial Intelligence (AI) presents a significant strategic challenge for organizations, extending far beyond technical implementation. While AI offers transformative potential for operational efficiency and decision-making, its adoption is fraught with critical issues. These include widespread employee resistance to change, fears of job displacement, significant digital skill gaps, and profound ethical concerns regarding responsible use. This study argues that effective leadership is the pivotal factor in navigating these challenges. Through a qualitative review of academic literature, industry reports, and case studies, this paper examines the essential leadership competencies required to support the integration of AI. We identify key leadership roles in strategic planning, ethical governance, change management, and employee engagement. Our findings indicate that leadership, particularly through strategic vision and planning, is the critical success factor influencing AI adoption outcomes. The study concludes that leaders must be proactive in guiding digital transformation, building trust, and fostering a collaborative culture between humans and machines. Practical recommendations are provided for leadership development, focusing on enhancing digital literacy, implementing ethical frameworks, and ensuring AI integration promotes both organizational performance and human-centric values.